2017
DOI: 10.1007/978-3-658-17181-0
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation von Abgaswerten

Abstract: Zugriff auf tausende von Fachbüchern und Fachzeitschriften Selektion, Komprimierung und Verknüpfung relevanter Themen durch Fachredaktionen Tools zur persönlichen Wissensorganisation und Vernetzung www.entschieden-intelligenter.de Sichern Sie sich umfassendes Technikwissen mit Sofortzugriff auf tausende Fachbücher und Fachzeitschriften aus den Bereichen:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…ditions are more dynamic than the tested driving cycles. In addition, it is known that several manufacturers have installed software that manipulates the test results by reducing emissions specifically during the test procedure (Borgeest, 2017). This results in increased exhaust emissions during normal driving operation.…”
Section: Introductionmentioning
confidence: 99%
“…ditions are more dynamic than the tested driving cycles. In addition, it is known that several manufacturers have installed software that manipulates the test results by reducing emissions specifically during the test procedure (Borgeest, 2017). This results in increased exhaust emissions during normal driving operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, various studies (Carslaw et al, 2011;Chen and Borken-Kleefeld, 2014) have shown that the real driving conditions are more dynamic than the tested driving cycles. In addition, it is known that several manufacturers have installed software that manipulates the test results by reducing emissions specifically during the test procedure (Borgeest, 2017). This results in increased exhaust emissions during normal driving operation.…”
Section: Introductionmentioning
confidence: 99%